2020
DOI: 10.1108/ijebr-09-2019-0529
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of entrepreneurial employee activity: does gender play a role?

Abstract: PurposeThe objective of this article is to examine the extent to which the antecedents of entrepreneurial employee activity differ by gender across countries.Design/methodology/approachGeneralised linear multilevel logistic regression is applied to data from the Global Entrepreneurship Monitor (GEM) with a sample of 60 countries for the period 2014–2016. This data is complemented with data from the World Governance Indicators (WGI) project and from the International Monetary Fund (IMF).FindingsUsing human capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 108 publications
(144 reference statements)
0
24
0
Order By: Relevance
“…The paper provides empirical evidence that social norms, employee attitude towards intrapreneurship, perceived characteristics and ability and firm strategy incidental to entrepreneurial orientation play as crucial antecedents of employee intrapreneurial behaviour, which lead to their strategic renewal behaviour and venture behaviour. Organisational architecture, leadership and job design might play as subjective norms or institutional factors, are found to influence intrapreneurial behaviour (Chakrabarty, 2020; Fisher et al , 2020; Karatepe et al , 2020; Moghaddas et al , 2020; Turro et al , 2020). Employee attitude related to intrapreneurship such as job satisfaction, career goals at the company and motivations (income and independence) influences intrapreneurial behaviour (Antoncic and Antoncic, 2011; de Correia et al , 2019; Douglas and Fitzsimmons, 2013; Farrukh et al , 2017; Valsania et al , 2016; ul Haq et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The paper provides empirical evidence that social norms, employee attitude towards intrapreneurship, perceived characteristics and ability and firm strategy incidental to entrepreneurial orientation play as crucial antecedents of employee intrapreneurial behaviour, which lead to their strategic renewal behaviour and venture behaviour. Organisational architecture, leadership and job design might play as subjective norms or institutional factors, are found to influence intrapreneurial behaviour (Chakrabarty, 2020; Fisher et al , 2020; Karatepe et al , 2020; Moghaddas et al , 2020; Turro et al , 2020). Employee attitude related to intrapreneurship such as job satisfaction, career goals at the company and motivations (income and independence) influences intrapreneurial behaviour (Antoncic and Antoncic, 2011; de Correia et al , 2019; Douglas and Fitzsimmons, 2013; Farrukh et al , 2017; Valsania et al , 2016; ul Haq et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…al. ( 2020 ) in which the perceived consequences of failure refrain female employees from increasing their intrapreneurial engagement.…”
Section: Discussionmentioning
confidence: 99%
“…In this macro-environmental level with 35 % of reviewed studies, we found that several authors analysed the relationship between entrepreneurs and social, political, economic or institutional conditions. Concretely, this literature is related to works by Noguera et al (2013Noguera et al ( , 2015 and Turro et al (2020) that used the institutional approach to analyse the factors that affect female entrepreneurial activity in more developed contexts.…”
Section: Macro-environmental Levelmentioning
confidence: 99%